Decoupling Growth from Fossil Fuels? Energy Consumption and Structural Transformation in the GCC - Samreen, Sana; Shahee, Shaukat Ali (International Journal of Energy Economics and Policy, 2026)
The current study has tried to explore the impact of both renewable as well as non-renewable energy consumption on some of the crucial economic determinants like economic growth, export diversification, trade openness, and human capital in the GCC countries during the time period between 1990-2022. The most relevant second-generation panel econometric techniques, incorporating panel unit root tests, cointegration analysis, Fully Modified Ordinary Least Squares (FMOLS), and quantile regression, have been used. The comprehensive empirical analysis reveals that the consumption of renewable energy is quite significantly impacted by structural variables like trade openness and human capital, while on the other hand, non-renewable energy consumption is principally driven by short-run macroeconomic fluctuations, predominantly GDP and export diversification. The findings of this study highlight the importance of strategic policy realignment in the GCC to promote a sustainable energy transition by investing in human capital, enhancing trade openness, and decoupling economic diversification from carbon-intensive sectors. This paper further offers quite critical insights into the nexus between energy and economy and provides actionable policy recommendations for achieving long-term economic as well as environmental sustainability in fossil-fuel-dependent economies.